Sedation-related Adverse Events Associated with a Diagnostic Upper Endoscopy: A Single Center-observational Study - Jihyun Lee; Ki-Nam Shim; Kang Hoon Lee; Ko Eun Lee; Ji Young Chang; Chung Hyun Tae; Chang Mo Moon; Seong-Eun Kim; Hye-Kyung Jung; Sung-Ae Jung (Yong Chan Lee, 2017)
Background/Aims: Appropriate sedation during endoscopy can significantly reduce the discomfort experienced by a patient when the procedure is performed; however, it is associated with several potential risks. Very few reports describe sedation-related adverse events occurring during endoscopy. Our study evaluated the current status of sedation-related adverse events during a diagnostic upper endoscopy. Materials and Methods: We reviewed medical records of 5,564 cases of diagnostic upper endoscopy performed using midazolam for sedation at the Ewha Womans University, Mokdong Hospital, between January 2015 and March 2016. Results: Among the 5,564 cases, sedation-related adverse events were reported in 56 cases (1.0%). Among these 56 patients, 30 patients (53.6.%) were men and 26 patients (46.4%) were women. Mean age of the patients was 63.7±15.4 years. The most common adverse event reported was hypoxia, which was observed in 37 patients (0.7%). Other adverse events included sedation failure (18 patients, 0.3%) and delayed discharge from the recovery room due to delayed recovery of consciousness (one patient, 0.02%). Among patients presenting with hypoxia, 35 patients recovered after administration of intravenous flumazenil and oxygen via nasal prongs. Administration of oxygen alone helped recovery in 2 patients. All patients recovered uneventfully with no mortalities registered. Conclusions: Our study showed that the use of sedative midazolam is relatively safe during an upper endoscopy. The rate of occurrence of adverse events was very low, and no fatal adverse events were observed. However, close observation and continuous monitoring is an essential component of safe sedation during endoscopy.